2012
DOI: 10.1111/ger.12019
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ attitudes regarding oral health in a long‐term care institution in Brazil

Abstract: Caregivers' oral health practices are in accordance with good oral health methods and are not associated with difficulties in performing oral hygiene. However, the high number of elderly people in their care could possibly overwhelm caregivers' practices. Future qualitative assessment of these issues is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Research by Junges et al . reported the attitude of caregivers regarding oral health in a long‐term care institution in Brazil, and the results showed that 75% of the caregivers performed teeth brushing as part of their routine, but only 21% performed cleaning of the mucosa with gauze. However, when asked whether they would motivate the independent elderly to perform oral hygiene, only 41.7% of the caregivers responded positively.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Junges et al . reported the attitude of caregivers regarding oral health in a long‐term care institution in Brazil, and the results showed that 75% of the caregivers performed teeth brushing as part of their routine, but only 21% performed cleaning of the mucosa with gauze. However, when asked whether they would motivate the independent elderly to perform oral hygiene, only 41.7% of the caregivers responded positively.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions and attitudes by caregivers related to their own oral health influenced the care they provide to elders. If caregivers fail in this task of caring for their own oral hygiene, there would be a tendency to transfer the same attitudes to the person who is under their care 32 .…”
Section: Discussionmentioning
confidence: 99%
“…So that it is needed and becomes an essential consideration of the implementation of oral care, for that, we need guidelines, training, and education in terms of oral care (9). A previous study mentioned that only 41.7% of positive caregivers provide oral care for stroke patients treated (10). Another study described the benefits of oral cleansing on improving mouth freshness so that food becomes more delicious, and nutrition for patients can be fulfilled (11).…”
Section: Introductionmentioning
confidence: 99%